Carnot Cycle and Heat Engine Fundamentals and Applications II - Feidt, Michel (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This second Special Issue connects both the fundamental and application aspects of thermomechanical machines and processes. Among them, engines have the largest place (Diesel, Lenoir, Brayton, Stirling), even if their environmental aspects are questionable for the future. Mechanical and chemical processes as well as quantum processes that could be important in the near future are considered from a thermodynamical point of view as well as for applications and their relevance to quantum thermodynamics. New insights are reported regarding more classical approaches: Finite Time Thermodynamics F.T.T.; Finite Speed thermodynamics F.S.T.; Finite Dimensions Optimal Thermodynamics F.D.O.T. The evolution of the research resulting from this second Special Issue ranges from basic cycles to complex systems and the development of various new branches of thermodynamics.